An Investigation on Health Literacy and Its Impact on Health-Promoting Behaviors among the Residents of Mashhad - Mohammad Hasan Sharbatiyan (توسعه اجتماعی, 2024)
This research aims to assess the ability to acquire, analyze, and comprehend health-related information to make informed choices on activities that promote good health. Theoretical agency, focusing on opportunity and choice, has been suggested to investigate variables and explain results. The research approach used in this study is both descriptive and correlational. The statistical population under investigation consists of urban residents in Mashhad who are over 18 years old. The sample size of 650 individuals was picked using a multi-stage and simple random cluster method, considering each area's size. The data-gathering tool is a questionnaire that follows a set of established guidelines. The content validity and reliability coefficient of health literacy (0.822) and health-promoting behaviors (0.800) have been calculated. The findings of this study indicate that the overall condition of the dependent variable in urban regions could have been more beneficial. The contextual variables did not exhibit significant associations with the primary variables of the study. The main and sub-hypotheses exhibited a moderate to high degree of correlation and significance, with a p-value of less than 0.05. The beta regression findings indicate that the functional, relational, critical, and fundamental components significantly influence the dependent variable, with a percentage correlation value of 69% respectively. Furthermore, the prediction equation's findings indicate that 49% of the variability in the dependent variable can be accounted for. Additionally, the variable Health literacy directly affects health-promoting behaviors, with an effect size of around 0.865 units.